Hydrostatic Pressure Controls Angiogenesis Through Endothelial YAP1 During Lung Regeneration - Mammoto, Tadanori; Hunyenyiwa, Tendai; Kyi, Priscilla; Hendee, Kathryn; Matus, Kienna; Rao, Sridhar; Lee, Sang H.; Tabima, Diana M.; Chesler, Naomi C.; Mammoto, Akiko (Frontiers in Bioengineering and Biotechnology, 2022)
Pulmonary artery (PA) pressure increases during lung growth after unilateral pneumonectomy (PNX). Mechanosensitive transcriptional co-activator, yes-associated protein (YAP1), in endothelial cells (ECs) is necessary for angiogenesis during post-PNX lung growth. We investigate whether increases in PA pressure following PNX control-angiogenesis through YAP1. When hydrostatic pressure is applied to human pulmonary arterial ECs (HPAECs), the expression of YAP1, transcription factor TEAD1, and angiogenic factor receptor Tie2 increases, while these effects are inhibited when HPAECs are treated with YAP1 siRNA or YAP1S94A mutant that fails to bind to TEAD1. Hydrostatic pressure also stimulates DNA synthesis, cell migration, and EC sprouting in HPAECs, while YAP1 knockdown or YAP1S94A mutant inhibits the effects. Gene enrichment analysis reveals that the levels of genes involved in extracellular matrix (ECM), cell adhesion, regeneration, or angiogenesis are altered in post-PNX mouse lung ECs, which interact with YAP1. Exosomes are known to promote tissue regeneration. Proteomics analysis reveals that exosomes isolated from conditioned media of post-PNX mouse lung ECs contain the higher levels of ECM and cell-adhesion proteins compared to those from sham-operated mouse lung ECs. Recruitment of host lung ECs and blood vessel formation are stimulated in the fibrin gel containing exosomes isolated from post-PNX mouse lung ECs or pressurized ECs, while YAP1 knockdown inhibits the effects. These results suggest that increases in PA pressure stimulate angiogenesis through YAP1 during regenerative lung growth.